Growth Parameters of Exclusively Breastfed versus Non-Exclusively Fed Infants in the First 5 Months of Life before Introduction of Semi-Solid Foods - Gauchan, Eva (Birat Journal of Health Sciences, 2021)
Introduction: Exclusive breast-feeding has many advantages over nonexclusive feeding; better growth and lower risks of infections being most important. The aim of this study was to find the hospital prevalence of exclusive breast-feeding, find any differences in growth and morbidity patterns in babies who were exclusively breast-fed as compared to those who were not. Methodology: This was a hospital-based cross-sectional study over a period of one year which enrolled infants 1.5 months, 2.5 months, 3.5 months and 5 months of age who were on exclusive breast-feeding or non-exclusive feeding and who had not been started on semi-solid foods. Growth and morbidity patterns were recorded. Statistical analysis was done by SPSS version 25. Continuous variables were reported as median [IQR] while categorical variables were reported as absolute number (%). Mann-Whitney U test and Chi-square test were used to find the level of significance respectively. Results: The hospital prevalence of exclusive breast-feeding was found to be 62%. Weight for age was significantly higher in infants who were on exclusive breast-feeding (p=<.05) at 1.5, 2.5 and 3.5 months of age. Similarly length for age was higher in infants at 1.5 months (p=.034) of age but there after no difference was seen. Undernutrition was seen in 5.5% of non-exclusively fed infants as compared to 0.9% of exclusively breast-fed babies (p=<.001). Illnesses like pneumonia, diarrhea, ear infection and urinary tract infection were seen more in infants who were on nonexclusive feeding as opposed to infants who were exclusively breast-fed (p=<.05). Conclusions: Exclusively breast-fed babies have betier growth in terms of weight and lesser morbidities as compared to those babies who are non-exclusively fed.